An assessment of the sharps management practices in health care establishments in Pahang, Malaysia: organisational factor - Abdullah Suhaimi, Afiza; Samsuddin, Niza; A. Rahman, Nor Azlina; Jack, Kie Cheng; Sidek, Suriati (International Pharmaceutical Research, 2018)
The increasing number of healthcare services facilities to accommodate the needs of population growth especially in developing countries including Malaysia has definitely increase the prevalence of needle sticks injury (NSI) among the health care workers (HCWs). According to the World Health Organization (WHO), 35.7 million HCWs in the world are exposed to the risk of NSIs. Occupational Health Unit, Ministry of Health Malaysia reported an incidence rate of 4.7 NSI per 1,000 HCWs in 2005. Epidemiological studies indicate that a person who experience one NSI from a needle used on an infected patient has a risks of 30%, 1.8% and 0.3% of becoming infected with HBV, HCV and HIV respectively. Thus, an exploratory qualitative study was conducted to explore the current practices on sharps management in Health Care Establishments (HCEs) in Pahang. The study adopted thematic and coding descriptive analysis from focus group discussions and interview responses. The data were analysed by using NVivo – pro version 11. This manuscript will report only on the organizational factors as one of the major themes besides employee factors. Six codes that influence the cause of NSIs in the organizational factor theme include cost, policy and guideline, training, technology, safety and reporting issues. The study concluded that the most frequent and lengthy issues discussed by the participants were on the standard operation procedure, late reporting issues and safety aspect pertaining to the sharps management including the quality of personal protective equipment and vaccinations. Results suggest that all factors responsible for the above result should be addressed as a basis of national standard of sharps management for the betterment of HCWs safety in HCEs in Malaysia.